PENGEMBANGAN BELAJAR BERBASIS ANEKA SUMBER (BEBAS) - Eveline Siregar (Perspektif Ilmu Pendidikan, 2007)
The development of science and technology is improved rapidly brings about the sources of learning vary as well. This condition facilitates learners in studying independently. This article wants to discuss the definitions of the sources of learning, the technology types of the sources of learning, the benefits of the variety resource based learning, and the ways of learning and using the sources of learning.